A Comparative Study of the Use of Different Systems to Treat Cases of Delayed Ovulation in Cattle - Khamees , Hussein Abbas; Mshary , Ghasaq Sami; Emad Kadhum, Noor Almustafa (American Journal of Biomedicine and Pharmacy, 2025)
The study was designed to treat recurrent cases of failure of pregnancy in cows, resulting from delayed ovulation, using two treatment methods: hormonal and non-hormonal. The study included 20 cows, all of whom had a history of three or more failed inseminations, despite having a regular reproductive cycle and no apparent signs of uterine or reproductive inflammation. Cows showing signs of estrus were examined by rectal palpation 18 hours after the first sign of estrus. A follicle was observed on one of the ovaries, indicating delayed ovulation. The cows have been divided to two treatment groups: the first one included 10 cows treated with the human chorionic gonadotropin (hCG), while the second group included 10 cows treated with electrical stimulation. The results showed that ovulation occurred in the first group, and insemination and fertilization were successful in 90% of cases, while ovulation and fertilization were successful in the second group, 70% of cases. We conclude from this study that electrical stimulation can be used to stimulate ovulation at a rate almost as high as that of hormonal therapy. This indicates that ovulation requires hormonal stimulation and a neural reflex to occur. Furthermore, electrical stimulation is a safe, easy-to-use, and inexpensive method that only requires proper control.